Exchange Rate Volatility, Institutions and Growth: Evidence fiom Malaysia - Zainal, Zalina; Sarmidi, Tamat; Shaari MOhd Nor, Abu Hassan (2016)
Inspired by increasing evidence of nonlinear relationship of exchange rate and the importance to integrate the role of institutions, we have estimated the threshold value of exchange rate volatility in analyzing the relationship of exchange rate volatility, institutions and growth. The study is conducted on Malaysia, using quarterly data from 1984 to 2013. Further, the non-monotonicity relationship is analyzed by employing threshold regression adapted from Hansen (2000). The results suggest that there is an evidence of threshold effect in the relationship between exchange rate volatility and economic growth. Interestingly, the study finds that the negative effect of exchange rate volatility is reduced for countries with good institutions. The negative effect is effective only after certain level of volatility is archived. In conclusion, the study shows that the volatility of the exchange rate adversely affect economic growth and the effects vary according to the level of volatility, however good quality of institution is able to reduce the negative impact on economic growth.